THE ROLE OF MICRO CREDIT BANK TO INCREASE SMALL CAPITAL WORKING IN KARAWANG DISTRICT - Dedi Sudrajat (Value : Journal of Management and Business, 2017)
Amid the global economic outlook is still uncertain, the great challenge today is how to maintain sustainable economic growth in the future. Indeed, the Indonesian economy has a capital base to continue to grow continuously, because the Indonesian economy is tested more stable, sustained basis the growing middle class, as well as the availability of 'policy space' is sufficient to dampen the global risk. Even if Indonesia was able to answer some of the micro-structural constraints, especially the availability of basic infrastructure, Indonesia is believed to be able to grow at a higher trajectory again. Bank As a financial institution, the daily activities of the bank will not be separated from the financial sector. This study uses associative method, the most basic banking activities are buying money by collecting funds from the public. Then sell the money collected by channeling back to the community through the provision of pin-age or credit. SMEs are capable of helping small lembaa bank credit payment each month. This study was conducted to determine the problem that is on the SME. Key Words:Micro Credits, Bank, Capita Working, SME